Risk factors that affect condylar resorption after orthognathic surgery. Literature review - Guerra Erazo, Cristina Alexandra (2022)
Condylar resorption (CR) after orthognathic surgery (OS) is an undesirable consequence and sometimes with irreversible complications. The purpose of the research was to determine the risk factors that affect CR after OS by means of a literature review. For which an exploratory and documentary study was proposed, a literature review of the articles from 2000 to 2020 was carried out, without language restriction, excluding animal and in vitro research, conference abstracts, CR publications related to systemic disease and studies on condylar remodeling without specifying postoperative CR. The search for information was performed between July-August 2021, in Pubmed, Embase and SciELO databases, initially it was with the terms of CR, OS, progressive condylar resorption, “CR and OS”, reporting 1346 initial articles, then a selection of studies was made according to risk factors, identifying 53 articles, following the PRISMA guidelines. Twenty-three articles were included, the analysis of which showed that the main risk factors involved in postoperative CR are the female sex of the patients, between 14 and 58 years old, with Angle II class malocclusion, with high mandibular plane angles (24º - 50º), exposed to bimaxillar surgery, mandibular advancement (MA) greater than 5 mm counterclockwise, use of rigid intermaxillary fixation and that postoperative relapse can be related to CR.